Paradigm revolutions and discourse debates - Kramer, Sherianne (PINS-Psychology in Society, 2018)
[BOOK REVIEW] Parker, Ian (2015) Psychology after the crisis: Scientific paradigms and political debate. London: Routledge. ISBN 978-1-84872-207-1 pbk. 126 pages Parker, Ian (2015) Psychology after deconstruction: Erasure and social reconstruction. London: Routledge. ISBN 978-1-8487-209-5 pbk. 136 pages Parker, Ian (2015) Psychology after discourse analysis: Concepts, methods, critique. London: Routledge. ISBN 978-1-84872-211-8 pbk. 126 pages Critical and discursive psychology have long been the sites to contest the roles of language, institutional knowledge and power structures in the maintenance of the discipline of psychology. For over 25 years, Ian Parker has been a key leading figure in the development of these debates. Until now, some of the central ideas of this critical work have remained disparate and scattered, this dispersion being further reinforced by the sheer vastness and diversity of approaches that consider themselves “critical”. In his Routledge-series, Psychology after critique, for the first time, Parker brings together a reworked range of his most important papers to present a focused and radical presentation of key debates that he argues emerge from an early “paradigm crisis” in the psychological field. As a response to the general discontent with the laboratory experiment as the primary mode of framing, investigating and understanding the “psychological”, this crisis enabled the materialisation of qualitative research as a “paradigm revolution” that Parker argues paved the way for a critical and thus a political psychology, in both its conceptual and methodological forms.